If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -1x) = 9(15x + -5) (5 * 3 + -1x * 3) = 9(15x + -5) (15 + -3x) = 9(15x + -5) Reorder the terms: 15 + -3x = 9(-5 + 15x) 15 + -3x = (-5 * 9 + 15x * 9) 15 + -3x = (-45 + 135x) Solving 15 + -3x = -45 + 135x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-135x' to each side of the equation. 15 + -3x + -135x = -45 + 135x + -135x Combine like terms: -3x + -135x = -138x 15 + -138x = -45 + 135x + -135x Combine like terms: 135x + -135x = 0 15 + -138x = -45 + 0 15 + -138x = -45 Add '-15' to each side of the equation. 15 + -15 + -138x = -45 + -15 Combine like terms: 15 + -15 = 0 0 + -138x = -45 + -15 -138x = -45 + -15 Combine like terms: -45 + -15 = -60 -138x = -60 Divide each side by '-138'. x = 0.4347826087 Simplifying x = 0.4347826087
| x/8=54 | | 3.75+3y=6 | | f(x)=8-7(4x+2) | | 2x+9=1x+1 | | 6x+3(2x+2)=102 | | 31=x+2x+(3x+1) | | 2x^2-5x-12.5=0 | | 2x^2-5x-12.51=0 | | 5x+7y/3(x+y) | | -3x-4=-6-5x | | 3x+5(25-x)=89 | | 7x+12y=34 | | 2(x+2)=3(x+6) | | 7x+12y=86 | | 3x+5(25-5)=89 | | 4(X+1)-2=6(5-X)+3 | | -3-2(x+4)=25 | | ln(2x+6)=-10 | | f(x)=4-x^2+5x^2 | | 2/3x=-3/5 | | fx=4-x^2+5x^2 | | 3x+5(5x-8)=156 | | Y+a+b+c/6 | | -3+6x+x^2=0 | | 44=2(3x+4) | | 3(3x+9)=9x+27 | | 2x^2+3y-5x=-3 | | 5x+2=23-2x | | 4y(5y-2)=122 | | 4-(5X+7)=6-(X-3) | | 4yx(5y-2)=122 | | -b^4+5b^2+36=0 |